Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation terhadap Hasil Belajar Siswa dalam Pembelajaran PKn Kelas V SDN 10 2X11 Kayutanam - Sari, Indah Permata; Arwin, Arwin; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research aims to determine the effect of the use of cooperative learning model type group investigation on the results of learningPkn five grade students SDN 2X111 Kayutanam City. This research is a type of experimental research in the form of Quasi Experimental Type Nonequivalent Control Group Design. The sampling technique using cluster sampling technique with the sample number 40students consisting of 20 students of class VA and 20 students of class VB. The instrument used is a test.Based on the research that has been done, obtained t count> t table, (1,897626148>1,68595)with α = 0.05is means Ho is rejected and Ha accepted, it meaning there is influence the use of Group Investigation model of student learning outcomes in nets build a simple space VSDN 10 2X11 Kayutanam. Keyword :Group Investigation  model, learning outcomes